Strategi Pembelajaran Quantum dalam Meningkatkan Motivasi Belajar Peserta Didik - Rafika Hasanah; Reina Aulia Revi; Gusmaneli Gusmaneli (Islamic Sharia Coll, 2024)
In the world of modern education, concepts and principles will emphasize active interaction between teachers and students, the use of technology, and student freedom of exploration. The advantages of this strategy include the development of critical, creative thinking skills and the possibility of lifelong learning. However, challenges include complex assessments and managing dynamic learning environments. Writing this article provides in-depth insight into quantum learning strategies in education today.